Cancer Treatment Dosing Regimens of Zoledronic Acid Result in Near-Complete Suppression of Mandible Intracortical Bone Remodeling in Beagle Dogs - Allen, Matthew R (Wiley Subscription Services, Inc., A Wiley Company, 2010)
Bisphosphonate doses used in cancer treatment are substantially higher than those used for osteoporosis. Little is known about the effects of these high doses on tissue-level remodeling suppression. The aim of this study was to assess the effects of cancer dosing regimens of zoledronic acid on tissue-level bone remodeling at different skeletal sites. Skeletally mature female beagle dogs were treated with monthly intravenous infusions of vehicle (VEH, saline) or zoledronic acid (ZOL, 0.067 mg/kg); an additional group of animals was treated daily with oral alendronate (ALN, 0.2 mg/kg/day). Doses of ZOL and ALN were, on a milligram per kilogram basis, consistent with those used for cancer and osteoporosis, respectively. Following either 3 or 6 months of treatment, animals were euthanized, and mandible, rib, and tibia were processed for dynamic bone histology. There was no evidence of oral lesions or bone matrix necrosis in the mandibles of any animals. After 3 months, the rate of intracortical bone remodeling in the mandible was significantly suppressed with ZOL (−95%) compared with VEH; by 6 months, ZOL had produced nearly complete suppression (−99%) compared with VEH. ZOL also significantly suppressed remodeling in the rib cortex at both 3 (−83%) and 6 (−85%) months compared with VEH; tibia cortex bone formation rate was nonsignificantly lower with ZOL treatment (−68% to −75%). Remodeling suppression in ZOL-treated animals was significantly greater than in ALN-treated animals at both the mandible and the rib; ALN and VEH were not different for any of the assessed parameters at any of the sites. Compared across skeletal sites, the absolute level of remodeling suppression with ZOL treatment was significantly greater at sites with higher remodeling, whereas the percent reduction was similar among the sites. These results document nearly complete intracortical remodeling suppression resulting from monthly intravenous zoledronic acid dosing, with changes being most dramatic at the mandible. Copyright © 2010 American Society for Bone and Mineral Research